The unfolding story of dying tumor cells during cancer treatment - He, Sijia; Huang, Qian; Cheng, Jin (Frontiers in Immunology, 2023)
Generally, the demise of cancer cells in different ways enables the body to clear these harmful cells. However, cancer cells obtain unlimited replication and immortality from successful circumvention of cell death via various mechanisms. Some evidence suggests that treatment-induced dying tumor cells even promote cancer progression. Notably, therapeutic interventions to harness the immune system against tumor cells have shown complicated influences in clinics. Herein, there is an urgent need to clarify the underlying mechanisms that influence the outcome and regulation of the immune system during cancer treatment. In this review, we provide an account on the cell death modes and the relationship between dying tumor cells with tumor immune microenvironment during cancer treatment, focusing on immunotherapy, from mechanistic standpoint to emerging limitations and future directions.